Personal income tax in Estonia – who’s burden? Füüsilise isiku tulumaks – kelle koorem? - Trasberg, Viktor (Estonian Discussions on Economic Policy, 2012)
Despite many common features, the personal income tax (PIT) systems are broadly country specific and designed in accordance with society’s preferences. The paper focuses on PIT developments during the last decade in Estonia. There will be considered income dynamics and allocation of taxpayers to income groups. Also will be analyzed PIT burden distribution across the income earners groups and explained main factors, influencing effective tax rates. Also will be given overview and explained dynamics of various deductions, which adjust actual tax burden. Despite the existing flat tax system in Estonia, different deductions are implementing significant progression to the actual tax system.